Anatomical-clinical correlation of the patients examined - Cat, Juan M; Sica, Miguel A; Mata, Hermes; Kasdorf, Helmut (Cirugía del Uruguay, 1972)
In the course of current research on Hodgkin's dísease, the authors indicated exploratory laparotomy with splenectomy and liver and ganglionic biopsis, i'n 32 patients, 21 of wham had never been treated and 11 presented evolution. In the first group they found modification of the stage established by clinical and paraclinical procedure.s in 13 cases, the majority in a more advanced state than expected, but also (2) in a less advanced stage of the disease. In the second group, active foci were found, which had not appeared when ordinary procedures had been employed. Results obtained in each of the abdominal sectors studied ( spleen, ganglia and live.r) are analyzed in this paper and compared with those resulting from élassic procedures. It should be noted that: 1) the majority of splenic lesions could not have been suspected with clinical methods; 2) there was high incidence of Hodgkin-type adenopathies in locations outside the lymphographic area which it would have been impossible to detect by classic methods; 3) this study confirms that Jiver involvement is rare when ther-e is no splenic localization. In view of the importance .of arriving at a correct definition of the stage of the disease for the purpose of deciding upons the therapy to be applied -as well as the fact that splenectomy is the most efficien( type of treatment far this localization- the auhors favour sysematic application of laparotomy and splenectomy far the three first stages of Hodgkin's disease.